Synthesis and Biological Evaluation of Lipophilic 1,4-Naphthoquinone Derivatives against Human Cancer Cell Lines - Shao-Hung Wang; Chih-Yu Lo; Zhong-Heng Gwo; Hong-Jhih Lin; Lih-Geeng Chen; Cheng-Deng Kuo; Jin-Yi Wu (Molecules, 2015)
To examine the effect of hydrophobicity on the anticancer activity of 1,4-naphthoquinone derivatives, a series of compounds bearing a 2-O-alkyl-, 3-C-alkyl- or 2/3-N-morpholinoalkyl group were synthesized and evaluated for their anticancer activity against five human cancer cell lines in vitro. The cytotoxicity of these derivatives was assayed against HT-29, SW480, HepG2, MCF-7 and HL-60 cells by the MTT assay. Among them, 2-hydroxy-3-farnesyl-1,4-naphthoquinone (11a) was found to be the most cytotoxic against these cell lines. Our results showed that the effectiveness of compound 11a may be attributed to its suppression of the survival of HT-29. Secondly, in the Hoechst 33258 staining test, compound 11a-treated cells exhibited nuclear condensation typical of apoptosis. Additionally, cell cycle analysis by flow cytometry indicated that compound 11a arrested HT-29 cells in the S phase. Furthermore, cell death detected by Annexin V-FITC/propidium iodide staining showed that compound 11a efficiently induced apoptosis of HT-29 in a concentration-dependent manner. Taken together, compound 11a effectively inhibits colon cancer cell proliferation and may be a potent anticancer agent.